Muslims in Telangana A Discourse on Equity, Development, and Security - Sudhir, G.; Bari, M. A.; Khan, Amir Ullah; Shaban, Abdul (Dynamics of Asian Development, 2021)
XXXII, 389 p. 62 illus., 4 illus. in color.